Three pure chaperone proteins of Escherichia coli--SecB, trigger factor and GroEL--form soluble complexes with precursor proteins in vitro. - Lecker, S (1989)
Diverse studies of three cytoplasmic proteins of Escherichia coli--SecB, trigger factor and GroEL--have suggested that they can maintain precursor proteins in a conformation which is competent for membrane translocation. These proteins have been termed 'chaperones'. Using purified chaperone proteins and precursor protein substrates, we find that each of these chaperones can stabilize proOmpA for translocation and for the translocation-ATPase. These chaperones bind to proOmpA to form isolable complexes. SecB and GroEL will also form complexes with another exported protein, prePhoE. In contrast, these chaperones do not form stable complexes with a variety of soluble proteins such as SecA protein, bovine serum albumin, ovalbumin or ribonuclease A. While chaperones may transiently interact with soluble proteins to catalyze their folding, the stable interaction between chaperones and presecretory proteins, maintaining an open conformation which is essential for translocation, may commit these proteins to the secretion pathway.